Assessment of reference genes for real-time quantitative PCR normalization in Ilex paraguariensis leaves during drought - Acevedo, Raúl Maximiliano (2018)
Reverse transcription of RNA followed by real-time quantitative PCR (qPCR) is to date the most reliable method for gene expression studies. However, to control the errors introduced along the numerous experimental procedures, it requires a normalization using internal reference genes with stable expression. To address this issue, nine candidate reference genes were investigated in Ilex paraguariensis leaves subjected to water stress. To facilitate the selection, we analysed the real-time qPCR data with three different software programs. The obtained results support the conclusion that RNA polymerase associated protein rtf1 homolog (RTF) combined with any of the following pairs is the most suitable triad of genes to compute a normalization factor: elongation factor 1-alpha + tubulin alpha chain (EF1a + α-Tub), actin + cyclophilin 38 (ACT + CYP38), or cyclophilin 38 + vacuolar protein sorting-associated protein 18 homologs (CYP38 + VPS). Our analysis constitutes the first in-depth study to identify the appropriate reference genes for the quantification of transcription in Ilex paraguariensis leaves during drought and provides essential information for further gene expression studies in this tree species